Detection of bovine viral diarrhea –mucosal disease (BVD-MD) in buffaloes and cows using ELISA - Hasso, Saleem A.; Al-Rubaye, Khawlah M. Imran (The Iraqi Journal of Veterinary Medicine, 2012)
Out of 210 tissue samples (lung and lymph nodes ) collected from buffaloes examined by ELISA specific to(BVDV) Bovine Viral Diarrhea Virus antigen ten (10) samples were positive out of 160 lung tissue collected with (4.7%)and (3)positive sample were detected out of 50 lymph node tissue samples collected with (1.4%). Totally 13 positive samples with (6.1%) in buffaloes examined. The total positive tissue samples were divided to three age group. Group age one from (birth -6 month), group age two from (6-18 month) and group age three (18 month up). The positive samples were (1),(10) and (2) with (0.47%),(4.7%)and (0.95%)respectively that indicate the presence of BVD antigen in buffaloes (Bubals bubalis) .Out of (210) sera samples collected from buffaloes examined by ELISA specific to (BVDV) antibody (83) positive sera samples with (39.5%) in buffaloes. The positive serum samples were divided into three age groups, group age one from (birth -6 month ), group age two from (6-18 month) and group age three (18 month up ). The positive samples were (3), (60) and (20) with (1.4 %), (28.5%) and (9.5%) respectively in buffaloes. Out of (60) sera samples collected from cows examined by ELISA specific to (BVDV) antibody 21/60 positive samples with (35%) in cows.The positive serum samples divided to three age group ,group age one from (birth-6 month),group age two from(6-18 month) and group age three (18 month up ). The positive samples (1), (14), and (6) with (1.6%), (23.3%) and (10%) respectively. The result above indicated the presence of the disease as persistent infection (PI) in group one, (MD) in group two and (BVD) in group age three.